Emergency Medical Services Access and Patient Extrication: Operational, Safety, and Administrative Considerations for Health Security and Healthcare Leadership - Algaith, Tariq Mohammed; Ahmad Mohammed Alhajouj; Ayidh Mohammed Faraj Alghlfas; Sanad Burayk Aldawsari; Fahad Ali Mohammed Ghonemi; Ibrahim Mohsen Ali Khormi; Abdulaziz Abdullah Ibrahim Hamzi; Nawdh Mutair Almajdi (Saudi Journal of Medicine and Public Health, 2025)
Background: Emergency medical services (EMS) frequently operate in unstable, confined, and hazardous environments where rapid access and extrication are essential to patient outcomes and responder safety. Aim: To synthesize operational, clinical, and administrative considerations for safe patient access and extrication across diverse settings, and to outline evidenceinformed practices for EMS, health security leadership, and system administrators. Methods: Narrative integration of scene safety principles; environmental hazard mitigation; graded access techniques; delivery of medical care during entrapment (airway, circulation, spinal motion restriction, analgesia, hypothermia prevention); and highrisk, specialcircumstance procedures (crush injury protocols, early blood, impalement management, and lastresort field amputation). Results: Effective operations hinge on disciplined scene sizeup, stabilization of vehicles/structures, and interagency coordination to balance urgency with provider safety. Early, ongoing medical interventions during extrication—airway protection, ventilation, hemorrhage control, spinal alignment, analgesia, thermal management—reduce secondary injury. Crushinjury protocols prioritize prerelease fluid resuscitation and hyperkalemia mitigation; when available, early blood products should be initiated even during rescue. Automotive entrapments may require dash displacement or roof removal performed by trained teams adhering to standardized rescue practices. Postextrication, risks of hypothermia, metabolic derangement, hemorrhage, and airway compromise persist, necessitating vigilant reassessment and structured handover to receiving facilities. Conclusion: Treating extrication as a timesensitive medical intervention embedded within a highrisk operational context improves survival and safeguards responders. Systemlevel preparedness—policies, training, equipment, interagency agreements, and EMS physician engagement—underpins consistent, highquality performance.